DEVELOPMENT AND VALIDATION OF HPTLC METHOD FOR SIMULTANEOUS ESTIMATION OF TERBINAFINE HYDROCHLORIDE AND MOMETASONE FUROATE IN COMBINED DOSAGE FORM - Patel, Mehul M.; Shah, Heta D. (Journal of the Chilean Chemical Society, 2016)
A new simple, precise, accurate, specific and selective high performance thin layer chromatographic (HPTLC) method has been developed for the simultaneous estimation of Terbinafine hydrochloride (TH) and Mometasone furoate (MF) in cream dosage form. The chromatographic separation was achieved on Merck precoated silica gel aluminium plate 60 F254 using Toluene: Ethyl acetate: Glacial acetic acid (8: 4: 0.1 v/v) as mobile phase. The densitometric scanning was carried out at 248 nm. Response was found to be linear in the concentration range of 1000–3000 ng/band with correlation coefficient (r2= 0.999) for Terbinafine hydrochloride and 100-300 ng/band with correlation coefficient (r2= 0.998) for Mometasone furoate. All parameters of method, repeatability, precision, LOD, LOQ, % recovery were validated as per ICH guidelines. The proposed procedure was successfully applied for the simultaneous determination of both drugs in commercial cream preparation. The advantage of the method is simplicity, reasonable sensitivity, rapidity, excellent resolving power, low cost and is a more effective option than other chromatographic techniques in routine quality control.